Implementasi Good Corporate Governance pada Industri Perbankan Menuju Universal Banking - Rifqi Muhammad (Jurnal Aplikasi Bisnis, 2017)
The economic globalization has given impact to national banks since the existence of foreign banks in Indonesia. Foreign banks have better performance than national banks because they have intemational standardization of quality assurance. National banks still have internal problems such as;the weaknesses of organization, the lack of quality of human resources, and technology.National banks must compete not just locally but globally. They should implement good corporate governance in order to face global competition. This paper will explain the ways to develop good corporate governance in banking industry and several efforts to be universal banking.